Social Cognition in the Traditional Belis Marriage Tradition of the Sumba Community, East Nusa Tenggara (Van Dijk's Theory of Critical Discourse Analysis) - Riada, Marziana Welhelmina; Nensy Megawati Simanjuntak; Widya Desary Setia Wardhani (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
Indonesia is a country that is rich in culture and tradition. One of these cultural riches is in one region of Indonesia, namely East Nusa Tenggara. This cultural wealth is in the form of the Belis tradition which is expressed in the marriage process of the people of Sumba, East Nusa Tenggara. Belis is a symbol of marriage between men and women in East Nusa Tenggara. Belis is a dowry or a certain amount of money, goods or objects given by the prospective groom to the prospective bride. The amount of belis given usually follows the agreement or custom that applies in a particular community or tribe. Factors that influence the determination of the size of Belis are the social status of the family and the closeness of the relationship between the families. Usually the closer the kinship relationship, the greater the value of the belis that must be given. The inability to pay the belis results in social and psychological sanctions, namely being ostracized from society, being discussed by neighbors, being reprimanded by traditional leaders, and giving rise to a feeling of intense shame. This research is qualitative research with a phenomenological type